Curriculum guide for homemaking, grades 7 and 8 - Chicago Public Schools, IL.; Chicago Public Schools, IL. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1963)
The overall idea held is that the function of home economics is to help students identify and develop those fundamental competencies that will be effective in their personal and family living. A structure and framework upon which a teacher may establish an effective homemaking program for 7th- and 8th-grade girls and, at the same time, make the best possible use of the limited time available is presented. The courses have been divided into four broad units -- general survey, foods, clothing, and family living. These have been made flexible to adapt to different situations. Every effort should be made to provide maximum opportunity for this training because, for many students, these courses may be the only formal training for their future roles as family member, homemaker, and mother. Understandings, skills, attitudes, and appreciations for each unit are listed. Generalizations, vocabulary suggestions, and resource materials are included.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Child Care; Clothing Instruction; Curriculum Guides; Eating Habits; Family Life; Foods Instruction; Grade 7.; Grade 8.; Home Economics Education; Home Management; Homemaking Skills; Hygiene; Nutrition Instruction; Self Concept; Textiles Instruction; Unit Plan; Illinois (Chicago)